ASR, Volume 18, n° 2, 2014 - Full Issue - Journal System (African Sociological Review, 2016)
Contents Editorial .........................................................1 General Issues Cuban heritage in Africa: 19yh Century Deported Nanigos in Fernando to Isabela de Aranzadi 2 Isabela de Aranzadi ....................................................2 Essential medicines in Nigeria: Foregrounding. Chinwe Obuaku .............................................................44 Research Papers Rationalités nomades : Variabilité socio-écologique et résilience des Peuls pasteurs du Burkina Faso Gabin Korbéogo ............................................................63 A Few Good Men in a World of Gangsters: Discourses of Respectability and Risk amongst Student Teachers in the Western Cape, South Africa Fiona Larkan & Brian van Wyk ..................................84 Immigrant-Host Community Relations in Malawi’s Community based Rural Land development Project (CBRLDP) Paul Kishindo ..............................................................98 Le coupé décalé en Côte d’Ivoire : Sens et enjeux d’un succès musical Franck Gawa ................................................................108